Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Controls, Diagnostics and Instrumentation 2012
DOI: 10.1115/gt2012-69779
|View full text |Cite
|
Sign up to set email alerts
|

Precision Temperature Detection Using a Phosphorescence Sensor Coating System on a Rolls-Royce Viper Engine

Abstract: By adapting existing thermal barrier coatings a sensor coating has been developed to enhance their functionality, such that they not only protect engine components from the high temperature gas, but can now also measure the material temperature accurately and the health of the coating e.g. ageing, erosion and corrosion. The sensing capability is introduced by embedding optically active materials into the thermal barrier coating and by illuminating these coatings with excitation light phosphorescence can be obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The flattening of the curve at around 850°C is due to the electronics of the collection system and results in a reduced precision for measurements above this temperature. However, the temperatures of interest in this study and in the previous application of the sensor [13][14][15][16] are located in the steepest part of the curve as shown in Figure 2. …”
Section: Phosphorescence Calibrationmentioning
confidence: 98%
See 2 more Smart Citations
“…The flattening of the curve at around 850°C is due to the electronics of the collection system and results in a reduced precision for measurements above this temperature. However, the temperatures of interest in this study and in the previous application of the sensor [13][14][15][16] are located in the steepest part of the curve as shown in Figure 2. …”
Section: Phosphorescence Calibrationmentioning
confidence: 98%
“…The temperatures measured in the application of the TBC system in a Rolls-Royce jet engine [13][14][15][16] ranged from 500°C to about 650°C. The curve was obtained from over 500 data points, each consisting of 50 averaged single decays, recorded during the cooling down of the sample inside the furnace.…”
Section: Phosphorescence Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrometry and infrared thermography are good methods to detect creep, low-cycle fatigue, corrosion, erosion and oxidation [87,182]. Phosphor thermometry is able to identify failures such as cracks, erosion, corrosion and wear [183]. These techniques will be presented in detail in the next chapters.…”
Section: Hot Gas Component Monitoringmentioning
confidence: 99%
“…Feist et al showed in different publications the industrial application of phosphor thermometry. To develop these special paintings a Rolls-Royce jet engine was used for verification [183,200,201,202,203,204]. The application in an industrial gas turbine was proven as well.…”
Section: Hot Gas Component Monitoringmentioning
confidence: 99%